Design of Integrating Qalam AI and Language Teacher Competencies in Evaluating Arabic Reading Skill - Rizki, Restu Budiansyah; Rizal, Muhammad Fatkhur; Rahmawati, Chusnia (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
The development of technology in the field of education saw several advancements. One of these advancements was marked by the massive use of artificial intelligence technology, including in the evaluation of Arabic language learning. In response to this development, technological advancements had to be balanced with human competencies so that learning did not rely entirely on technology but was integrated with human thinking abilities. This research aimed to design an evaluation of Arabic reading skills based on the integration of Qalam AI and language teacher competencies. This study employed a descriptive qualitative approach, which was then practiced in learning through field experiments involving 150 respondents. Data collection methods include interviews, documentation, literature studies, and reading skill tests. The analysis used was descriptive analysis, as it focused solely on the evaluation design based on the integration of Qalam AI and language teacher competencies. Access to Qalam AI technology could be found at the website: https://qalam.ai/.  The results of the study indicated that the design of the evaluation for Arabic reading skills based on the integration of Qalam AI and language competencies could be simulated in six stages: 1) Arabic language learning based on Qalam AI, 2) Arabic reading skill tests, 3) Utilization of Qalam AI, 4) Application of language teacher competencies, 5) Diagnosis and placement, 6) Evaluation.